PENYERTAAN DALAM TINDAK PIDANA KORUPSI (TELAAH TERHADAP KELALAIAN DALAM PENYERTAAN UNTUK MELAKUKAN TINDAK PIDANA KORUPSI) - Hidayat, Reza (Katalogis, 2015)
This research is aimed to acknowledge the following issues, the position of police institution in the system of Indonesian governance. Through normative research, using legal sources from written laws and literatures related to police issues. Based on the research, it is found that, The position of Indonesian police institution under the President’s ruling is not effective yet, because of the President himself has been very busy with his duties on governing. The constitution of 1945 doesn’t state anything about the position of police institution under the President. The recommendations from this research are: to revise on the clause of the position of police institution under the President as mentioned in article 8 (1) Act No.2/2002 about Indonesian Police, and to form a new ministry named the ministry of safety to lead the Indonesian police institution directly